Peredaran Narkotika Tanpa Kontak Langsung: Studi Kriminologis terhadap Modus “Menempel” di Kawasan Lorong Jati Kota Kendari - Alasman Mpesau; Aldin; Ruslan; Ayib Rosidin (Jurnal Hukum Lex Generalis, 2026)
Narcotics trafficking in the Lorong Jati area of Kendari City has evolved through a contactless method known locally as "menempel" (sticking/placing) a "dead drop" mechanism where illicit goods are secretly deposited for the buyer to retrieve without ever meeting the dealer face-to-face. This study aims to conceptualize the "menempel" method as a crime script, identify the criminogenic factors driving its emergence and formulate criminological implications for redesigning control strategies. Employing a normative-empirical approach, the study analyzes this method through the frameworks of crime script analysis, Routine Activity Theory and Crime Prevention Through Environmental Design (CPTED). The findings reveal that the "menempel" method comprises four stages digital negotiation, placement, retrieval and payment deliberately separated in time and space to avoid detection in flagrante delicto. Its emergence is driven by the interplay of individual factors (economic pressure, peer influence), environmental factors (lack of surveillance and informal social control) and law enforcement factors (resource limitations and evidentiary challenges). The study recommends restructuring control strategies by expanding the scope of spatialcyber criminology, implementing intelligence-led policing, focusing interventions on networks and integrating CPTED with community participation.